Becoming Black creating identity in the African diaspora - Wright, Michelle M. (Durham Duke University Press, 2004)
Becoming Black is a powerful theorization of Black subjectivity throughout the African diaspora. In this unique comparative study, Michelle M. Wright discusses the commonalties and differences in how Black writers and thinkers from the United States, the Caribbean, Africa, France, Great Britain, and Germany have responded to white European and American claims about Black consciousness. As Wright traces more than a century of debate on Black subjectivity between intellectuals of African descent and white philosophers, she also highlights how feminist writers have challenged patriarchal theories of Black identity.
Includes bibliographical references (p. [261]-268) and index.
Keywords: Blacks--Race identity